Stress and the domestic cat: have humans accidentally created an animal mimic of neurodegeneration? - Niesman, Ingrid R. (Frontiers in Neurology, 2024)
Many neurodegenerative diseases (NDD) appear to share commonality of origin, chronic ER stress. The endoplasmic reticulum (ER) is a dynamic organelle, functioning as a major site of protein synthesis and protein posttranslational modifications, required for proper folding. ER stress can occur because of external stimuli, such as oxidative stress or neuroinflammatory cytokines, creating the ER luminal environment permissive for the accumulation of aggregated and misfolded proteins.Unresolvable ER stress upregulates a highly conserved pathway, the unfolded protein response (UPR). Maladaptive chronic activation of UPR components leads to apoptotic neuronal death. In addition to other factors, physiological responses to stressors are emerging as a significant risk factor in the etiology and pathogenesis of NDD. Owned cats share a common environment with people, being exposed to many of the same stressors as people and additional pressures due to their "quasi" domesticated status. Feline Cognitive Dysfunction Syndrome (fCDS) presents many of the same disease hallmarks as human NDD. The prevalence of fCDS is rapidly increasing as more people welcome cats as companions. Barely recognized 20 years ago, veterinarians and scientists are in infancy stages in understanding what is a very complex disease. This review will describe how cats may represent an unexplored animal mimetic phenotype for human NDD with stressors as potential triggering mechanisms. We will consider how multiple variations of stressful events over the short-life span of a cat could affect neuronal loss or glial dysfunction and ultimately tip the balance towards dementia.